Response of human dental pulp to dentin adhesive systems - Costa, CAS; Hebling, J. (Quintessence Publishing Co Inc, 2002)
Many in vivo studies have stated that the response of the dentin/pulp complex does not depend on the dental material used as the liner or pulp-capping agent. However, several in vitro studies have reported the metabolic cytotoxic effects of resin components applied to fibroblast and odontoblast cell lines. The aim of this study was to evaluate the human pulp response following direct pulp capping with current bonding agents and calcium hydroxide (CH). Sound premolars scheduled for orthodontic extraction had their pulp tissue mechanically exposed. After hemorrhage control and total acid conditioning, the experimental bonding agents, including All Bond 2, Scotchbond MP-Plus, Clearfil Liner Bond 2, and Prime & Bond 2.1 were applied on the pulp exposure site. CH saline paste was used as the control pulp-capping agent. All cavities were restored with Z-100 resin composite according to the manufacturer's instructions. Following extractions, the teeth were processed for microscopic evaluation. In the short term, the bonding agents elicited a moderate inflammatory pulp response with associated dilated and congested blood vessels adjacent to the pulp exposure site. A mild inflammatory pulp response was observed when Clearfil Liner Bond 2 or CH was applied on the pulp exposures. With time, macrophages and giant cells engulfing globules and components of all experimental bonding agents displaced into the pulp space were seen. This chronic inflammatory response did not allow complete pulp repair, which interfered with the dentin bridge formation. Pulp exposures capped with CH exhibited an initial organization of elongated pulp cells underneath the coagulation necrosis. CH stimulated early pulp repair and dentin bridging that extended into the longest period. The bonding agents evaluated in the present study cannot be recommended for pulp therapy on sound human teeth.